Analysis of Production Performance of Supply Chain Operation Reference in PT. Premier Doughnut Indonesia - Adhi, Christian; Santoso, Sugeng (International Humanities and Applied Science Journal, 2021)
This study aims to analyze the company's production performance using the SCOR (Supply Chain Operation Reference) method by looking at the reliability and responsiveness attributes using Perfect Order Fullfilment (POF) and Order Fullfilment Cycle Time (OFCT) metrics. Respondents in this study were Production Managers, Operation Managers, Kitchen Admins, District Managers and also Store Managers or Persons in Charge at 35 Krispy Kreme Indonesia stores. The place of observation is in the Central Kitchen of Krispy Kreme Indonesia, which is located in Taman Tekno, Tangerang, Banten. The results of this study found that the weakness of the production machine and the lack of a distribution fleet were the main influences on the lack of and late delivery of donuts to each store during a major promotion.